The male factor in infertile couples hundred Peruvians - Ascenzo Cabello, Jorge (2015)
In the first 100 private cases, between 1950-1952, we performed 102 spermatodiagnosis in 62 patients. Results: 72.5% of the specimen were obtained by coitus interrupts and 27.4% by masturbation. We found: Low liquefaction in 15.6%. Complete oligospermia in 7.8%. Pyospermia in 10.7%. On the other hand only 28% hand 100% or more fecundant power. The 38.2% between 51 to 99% of fecundant power. The remaining 33.3%, wich is a considerable percentage, had a fecundant power between 0% to 50% with 5 cases of azoospermia (7.9%). Treatment: We treated 25 cases with intramuscular serum gonadotropin with an average of 20.000 I.U. each one and rate of 400 U.I. daily with one day rest every 3 or 4 days.In 15 patients we added strong doses of vitamins A and C or E. As far as the spermatozoa is concerned the increase in number was remarkable but not the motility. The treatment was not sucessful on sperms with 20% or less of fecundant power. In the third of the cases in which the fecundant power was initially 50% or more, the treatment gave great deal of capacity of spermatic fecundation. In more then 60& of the cases the pregnancy appeared in this last group.